Pierre Robin sequence: Management of respiratory and feeding complications during the first year of life in a tertiary referral centre. Issue 8 (August 2015) - Rathé, M.; Rayyan, M.; Schoenaers, J.; Dormaar, J.T.; Breuls, M.; Verdonck, A.; Devriendt, K.; Poorten, V. Vander; Hens, G.
Abstract Objectives To review early clinical manifestations of Pierre Robin sequence (PRS) and their management during the first year of life in the University Hospitals Leuven. Methods Retrospective series of 48 patients with PRS born between 2001 and 2011 and treated at a tertiary referral hospital. Review of the current literature about management of respiratory and breathing difficulties in the early life of PRS patients. Results Of our cleft palate patients 15.3% presented with PRS. A syndrome was diagnosed in 14.6%, associated anomalies without a syndromic diagnosis in 56.3% and isolated PRS in 29.2% of the cases. Mortality rate directly related to PRS was 2.1%. Respiratory difficulties were observed in 83.3% and feeding difficulties in 95.6% of the patients. Respiratory problems were addressed in a conservative way in 75%, in a non-surgical invasive way in 42.5% and in a surgical way in 12.5%. A statistically significant relationship between the association of a syndrome or other anomalies, and a higher need for resuscitation and invasive treatment were found (chi-square test, p-values = 0.019 and 0.034). Feeding difficulties were managed conservatively in 91.3%, invasively in 80.4% and surgically in 15.2%. Conclusions PRS is frequently associated with other abnormalities or syndromes. Therefore routine screening for associated anomalies in neonates with PRS is recommendable. Respiratory and feeding complications are highly frequent and possibly severe, particularly in patients with associated anomalies or syndromes, and should be recognized and addressed appropriately in an early stage. There is a potential role for the nasopharyngeal airway in reducing the need for the more traditional surgical interventions for respiratory problems.